Inferior outcomes and treatment disparities in elderly patients with classical Hodgkin lymphoma: a national cancer data base analysis. Issue 5 (16th April 2019) - Major, Ajay; Jackson, Matthew W.; Smith, Derek E.; Kamdar, Manali; Rabinovitch, Rachel
Abstract: Elderly patients with classical Hodgkin lymphoma (cHL) are understudied and poorly defined. The National Cancer Data Base was queried for adults with cHL diagnosed 2004–2013: 22, 547 age 18–39, 12, 841 age 40–59, and 10, 873 age ≥60 were identified. Two-year overall survival (OS) was 97%, 91%, and 65% for the three age cohorts, respectively ( p  < .0001). Elderly patients age ≥60 had greater advanced comorbidity scores, stage III–IV disease, and lymphocyte-depleted histology. Elderly patients were treated less with chemotherapy, radiotherapy for stage I–II disease, and at academic/research centers ( p  < .001). There was improved OS in elderly patients who received chemotherapy and/or radiotherapy and were treated at academic/research centers. This largest analysis of elderly cHL demonstrates that patients ≥60 are distinct from those 40–59. Age ≥60 should be a stratification in future trials and merit distinct studies. Improving the poor rate of treatment delivery and directing care to academic centers may improve outcomes.